The impact of specialized training on certain motor skills and accuracy in performing the lay-up shooting skill for young basketball players. - Shehaib, L.Dr. Hadeel Taleb Mohammed; Farhan, L.Dr. Alia Hussein (Sulaimani Journal for Humanities, 2026)
The current study aimed to identify the effect of specialized exercises on certain motor abilities and the accuracy of the lay-up shot skill among young basketball players. The researchers used the experimental method, designing an individual experimental group. The research sample consisted of (12) young players representing the Al-Karkh Sports Club's youth team, aged (15-17). After implementing the main study procedures and analyzing the results, the researchers drew several conclusions, the most important of which is that specialized exercises played a significant role in developing certain motor abilities and the accuracy of the lay-up shot in basketball for young players. The researchers made several recommendations, including the necessity of using specialized exercises in training sessions due to their effective impact on developing certain motor abilities related to basketball skill performance.
Keywords: Specialized exercises; sensorymotor abilities; accuracy; and peaceful aiming